PENGEMBANGAN PERAN KEPALA SEKOLAH SEBAGAI LEADER DALAM MENINGKATKAN KINERJA GURU - Asep Saepul Hidayat; Herlina (LPPM Universitas Cipta Mandiri, 2025)
Starting from the study of the problem of low teacher performance improvement, and the importance of the role of the principal, this study focuses on the study of the development of the role of the principal as a leader in improving teacher performance. This study was conducted using a descriptive analytical method and a qualitative approach and process design as in qualitative research. The study concluded the following: (1) The problem of teacher performance in implementing the management of the learning process, essentially stems from the limitations of the external personal conditions of teachers, especially in the aspect of limited support for teacher work creativity; (2) The role of the principal as a leader in improving teacher performance, essentially provides support, direction, motivation, assistance and guidance to teachers to continuously and sustainably carry out the process of improving the capacity and competence of teachers and develop performance in a direction that is in accordance with the demands of existing needs in accordance with education quality standards; and (3) The development of the role of the principal as a leader in improving teacher performance, at this time, tends to develop aspects of: (a) Development of leadership strategies; (b) Development of technical leadership towards improving teacher performance based on the application of ICT media, information system management and conservation of local and national cultural values, especially in the application of character education; (c) Development of situational and democratic leadership styles; (d) Development of leadership roles oriented towards empowerment, cooperation, increasing loyalty, creativity and teacher work productivity.